CORRELATION OF FASTING AND POSTPRANDIAL GLUCOSE TO GLYCOSYLATED HEMOGLOBIN IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Ekadamayanti, Agustia Sukri; Sucipto, Krishna Wardhana; Zufry, Hendra; Firdausa, Sarah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Glycosylated hemoglobin (HbA1C) remains the gold standard for assessment of glycemic control, but in minimal resource setting, HbA1C become unavailable, hence it’s necessary to determine whether fasting (FPG) or postprandial (PPG) plasma glucose act as a better predictor for assessing glycemic control. This study was conducted to define relationship between plasma glucose and HbA1C. METHODOLOGY This retrospective observational study was conducted in private diabetes clinics in Banda Aceh, Indonesia. All subjects were patients with T2DM, and previous FPG, PPG and HbA1C measurements were collected. We used Pearson’s correlation analysis to find the statistical significance. RESULTS From 904 FG, PPG and HbA1C measurements, only 50 measurements that were performed at the same time can be included in the analysis. There were 30 (60%) males and 20 (40%) females, age 52,3±10,52 years. Mean FPG, PPG and HbA1C were 165±78 mg/dl, 239±122 mg/dl and 8,5±2,9% respectively. We divided subjects into 3 groups based on HbA1c, <7%, 7-9%, >9%. Mean FPG based on group was 97±15 mg/dl, 145±32,80 mg/dl, and 237±59,80 respectively. Mean PPG was 131±47,08 mg/dl, 210±65,63 mg/dl and 351±79,8 mg/dl respectively. Both FPG and PPG have positive correlation with HbA1C but higher correlation was found between PPG and HbA1C. CONCLUSION PPG has a closer association with HbA1c. Hence, PPG value contributed more to HbA1c level than FPG. Therefore, PPG should be a preferred method for glucose monitoring in the absence of HbA1c.